Within-subject, double-blinded, randomized, and placebo-controlled evaluation of the combined effects of the cannabinoid dronabinol and the opioid hydromorphone in a human laboratory pain model - Dunn, Kelly E.; Bergeria, Cecilia L.; Huhn, Andrew S.; Speed, Traci J.; Mun, Chung Jung; Vandrey, Ryan; Campbell, Claudia M. (Neuropsychopharmacology (New York, N.Y.), 2021)
This Phase II study evaluated analgesia, abuse liability, and cognitive performance of hydromorphone and oral delta-9-tetrahydrocannabinol (THC; dronabinol) using a within-subject, double-blind, randomized, placebo-controlled, human laboratory trial. Healthy adults ( N = 29) with no history of drug use disorder received combinations of placebo, hydromorphone (4 mg; oral), and dronabinol (2.5 mg, 5.0 mg, 10 mg; oral). Primary outcomes were quantitative sensory testing (QST) measures of acute (thermal, pressure pain; thermal, punctate probe temporal summation; cold pressor; conditioned pain modulation) and chronic pain (capsaicin 10% topical cream with thermal rekindling), measures of drug abuse liability, cognitive functioning, and adverse events. Subgroup analyses were conducted within opioid-responders (endorsed >20 on a Drug Effect visual analog scale during the hydromorphone-only condition) and nonresponders. A consistent dose-effect relationship of dronabinol on hydromorphone across all measures was not observed. Analgesia only improved in the hydromorphone + dronabinol 2.5 mg condition. Hydromorphone + dronabinol 2.5 mg showed the lowest and hydromorphone+dronabinol 5 mg showed the highest risk for abuse. Hydromorphone+dronabinol 10 mg produced a high rate of dysphoric effects, and hydromorphone+dronabinol 5 mg and hydromorphone + dronabinol 10 mg produced AEs. Subgroup analyses showed subjective effects and abuse risk was increased among opioid responders and largely absent among nonresponders. Overall, only hydromorphone+dronabinol 2.5 mg modestly enhanced hydromorphone-based analgesia and hydromorphone + dronabinol 5 mg and 10 mg increased risk for abuse and AEs. These data can help inform opioid-sparing efforts in clinical pain populations. Demonstration that potential opioid effects varied as a function of participant opioid sensitivity (e.g., responder status) is a novel finding that warrants additional research.